2017
DOI: 10.3389/fnmol.2017.00202
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Impairs Vesicular Secretion in Neuronal and Astrocyte Peptidergic Transmission

Abstract: Regulated secretion of neuropeptides and neurotrophic factors critically modulates function and plasticity of synapses and circuitries. It is believed that rising amyloid-β (Aβ) concentrations, synaptic dysfunction and network disorganization underlie early phases of Alzheimer’s disease (AD). Here, we analyze the impact of soluble Aβ1–42 assemblies on peptidergic secretion in cortical neurons and astrocytes. We show that neurons and astrocytes differentially produce and release carboxypeptidase E (CPE) and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…29 Because CPE and SgIII are essential in the processing and targeting of neuropeptides and neurotrophins, their participation in the pathological progression of AD may be suggested. 30 SgIII was expressed in the retina, where it acted as an angiogenic factor in diabetic retinopathy. 31,32 Furthermore, SgIII has been suggested to be involved in signal transduction in neurotoxin-induced apoptosis in dopaminergic neuroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…29 Because CPE and SgIII are essential in the processing and targeting of neuropeptides and neurotrophins, their participation in the pathological progression of AD may be suggested. 30 SgIII was expressed in the retina, where it acted as an angiogenic factor in diabetic retinopathy. 31,32 Furthermore, SgIII has been suggested to be involved in signal transduction in neurotoxin-induced apoptosis in dopaminergic neuroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…It is previously reported that Aβ can induce impairments in release of neurotransmitter or peptides from presynaptic terminals [ 33–35 ], including at inhibitory synapses [ 21 ], but it is unknown if this will affect synaptic dynamics. Presynaptic defects may be specifically important in AβPP-expressing GABAergic neurons [ 25, 26 ], which axons are presumably exposed to the highest Aβ levels.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory boutons can rapidly appear and disappear along the axon in response to changes in activity or molecular signals [ 14, 30–32 ]. Aβ toxicity has been reported to specifically induce presynaptic impairments [ 33–36 ], including at inhibitory synapses [ 21 ], but it is unknown if Aβ interferes with synaptic dynamics in inhibitory axons.…”
Section: Introductionmentioning
confidence: 99%
“…We propose that mirtazapine can exert protective effects against Aβ injury by acting on dendritic trafficking mechanisms that are required for the proper functioning of the anterograde secretory pathway as well as retrograde retromer trafficking in dendrites. Previous studies have shown that Aβ oligomers and neuroinflammation associated with AD impair axonal and dendritic retromer trafficking of BDNF, causing a downregulation in neurotrophin signaling, essential for neuronal development and maintenance of dendritic complexity ( Poon et al, 2011 ; Gan and Silverman, 2016 ; Seifert et al, 2016 ; Carlos et al, 2017 ; Plá et al, 2017 ). In hAPP transgenic mice, the impairment in axonal retrograde trafficking induced an aberrant retention of endosomes in distal neurites and impaired endosome-TGN and lysosomal functioning ( Tammineni et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant folding and accumulation of the amyloid-β peptide (Aβ), an hallmark of AD, causes neurite degeneration, synapse loss, and impairment in neuronal trafficking ( Serrano-Pozo et al, 2011 ; Plá et al, 2017 ). In the present study, using a live imaging approach on hippocampal neurons in culture, we investigate how Aβ 25 – 25 oligomers affect the dynamics of pGOLT-expressing vesicles indicative of Golgi-related organelles, such as Golgi outposts and satellites ( Horton and Ehlers, 2003b ; Horton et al, 2005 ; Mikhaylova et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%